Establishment and Validation of a Non-Invasive Diagnostic Nomogram to Identify Spontaneous Bacterial Peritonitis in Patients With Decompensated Cirrhosis - Xiang, Shoushu; Tan, Juntao; Tan, Chao; Xu, Qian; Wen, Yuanjiu; Wang, Tiantian; Yang, Chen; Zhao, Wenlong (Frontiers in Medicine, 2022)
Background and Aims：Spontaneous bacterial peritonitis (SBP) is a common and life-threatening infection in patients with Decompensated cirrhosis (DC), with high mortality and morbidity. However, due to the lack of typical symptoms or the low compliance and positivity of the ascites puncture test, SBP cannot be diagnosed early. We aimed to establish and validate a non-invasive diagnostic nomogram to identify SBP in DC patients. Method：A collection of 4475 patients with DC from July 2015 to December 2019 in Chinese A and B top three hospitals DC patients were divided into SBP group (1020 cases) and non-SBP group (3455 cases) according to whether the patients had SBP during hospitalization. 70% (2644 cases) of patients in hospital A were randomly selected as the training set, the remaining 30% (1134 cases) were used as the internal validation set, and patients in hospital B (697 cases) were used as the external validation set. Univariate analysis and lasso regression were used to screen variables, and logistic regression was used to determine independent predictors to construct a nomogram to identify SBP patients. We use AUC, calibration curve, and DCA to determine the effectiveness of the nomogram. Result：The nomogram was composed of 7 variables: longer hospital stays (OR=1.019,95%CI:1.010-1.029); Longer prothrombin time (OR=1.032,95%CI:1.006-1.060); Lower lymphocyte percentage (OR=0.954,95%CI:0.941-0.966); Lower prealbumin (OR=0.991,95%CI:0.988,0.994); Higher total bilirubin (OR=1.003,95%CI:1.001-1.004); Abnormal C-reactive protein (OR=1.616,95%CI:1.272-2.050); Abnormal procalcitonin levels (OR=2.107,95%CI:1.611-2.748). Good discrimination of the model was observed in the internal validation sets and the external validation sets (AUC = 0.786 and 0.712, respectively). The calibration curve result indicates that the nomogram was well-calibrated. The DCA curve demonstrates that the DCA map of the nomogram has good clinical application ability. Conclusion：This study identified the independent risk factors of SBP in DC patients and used them to construct a nomogram which may provide clinical reference information for diagnose SBP in DC patients.